The Impact of Histologic Variants on FSGS Outcomes - Meliambro, Kristin (Int Sch Res Notices, 2014)
Focal segmental glomerulosclerosis (FSGS) is the most common glomerular disease leading to end-stage renal disease. The clinical course is highly variable with disparate responses to therapeutic intervention and rates of progression. Histologic variant subtype has been commonly used as a prognostic and therapeutic guide in the clinical management of FSGS. The tip lesion is widely considered to portend the most favorable prognosis and to be the most responsive to steroid therapy. Conversely, the collapsing lesion, more prevalent in patients of African descent, is associated with steroid resistance and higher risk of disease progression. In the 10 years since the Columbia classification system for FSGS was published, some retrospective and one prospective study explored the impact of histologic variants at the time of biopsy on FSGS outcomes. The results largely validate its clinical predictive value with respect to treatment response, though its utility in cases recurring after kidney transplantation is still unknown. Sampling and interpretation errors are additional sources of caution. More research is needed to fully define reproducible prognostic and therapeutic markers for this polymorphic disorder.